The addresses of Pope Pius XII and the purposes of punishment following the latest reform of canon penal law - Kłosiński, Dariusz (Studia Teologiczne Białystok Drohiczyn Łomża, 2025)
The latest reform of canon law has brought significant and varied changes to Book VI of the Code of Canon Law, including the reorganization of the purposes of canonical punishment. This article analyzes the three purposes and their role in the application of canonical punishment at the procedural level. The topics addressed are also compared and explored in depth based on the allocutions of Pope Pius XII, which represent the sources of can. 1341 CIC, which lists the three purposes.